Validation of a Brief Seven-Item Response Bias-Free Geriatric Depression Scale - Broekman, Birit F.P.; Niti, Matthew; Nyunt, Ma Shwe Zin; Ko, Soo Meng; Kumar, Rajeev; Ng, Tze Pin (The American journal of geriatric psychiatry, 2011)
Shortened versions of various depression scales have typically been based on conventional techniques such as factor analysis, without simultaneously considering the removal of culturally biased items that show differential item functioning (DIF). The authors recently showed that eight items in the 15-item Geriatric Depression Scale (GDS-15) evidenced DIF, associated with gender, age, ethnicity, and chronic illnesses. By selecting out these items, the authors derived a shortened 7-item GDS and compared it with derivations based on conventional factor analysis and logistic regression techniques and validated its test performance in Asian elderly. The GDS-15 and Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, diagnosis of major depressive disorder (MDD) was independently administered by interviewers to 4,253 noninstitutionalized community-living elderly subjects aged 60 years and older. Concurrent methods of data reduction and item selection included factor analyses and logistic regression modeling. The GDS-7 was compared with GDS-15 test performance using Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders diagnosis of MDD as gold standard criterion and receiver operating characteristics analysis. After removal of eight DIF items, the derivation was consistent with and complements the results from factor analysis and logistic regression analyses. The short GDS-7 fit a unidimensional model with high explained total variance and demonstrated high sensitivity (0.93) and specificity (0.91) at a cutoff of one-half that was comparable with GDS-15. By removing items with culturally based response bias, the GDS-7 showed excellent scaling and test performance for screening MDD in an Asian elderly population.